The reproductive cycle of Callinectes danae Smith, 1869 (Decapoda, Portunidae) in the Ubatuba Region, Brazil - Costa, T. M.; Negreiros-Fransozo, M. L. (Brill Academic Publishers, 1998)
Callinectes danae Smith, 1869, known as siri-azul, is an important fishery resource along the Brazilian coast. The reproductive cycle of this species was studied based on their moult cycle and the development of their gonads. The animals were collected with an otter-trawl in the Ubatuba region (23 degrees 26'S 45 degrees 02'W) every other month from July 1991 to May 1993. A total of 1826 specimens were captured: 788 males and 1038 females. Ovigerous females and specimens with developed gonads in both sexes were found in all months sampled. In females, moult activity was recorded in all size classes while in males, it was verified from 20-27 mm to 90-97 mm size classes. The females produced more than one clutch during a single reproductive season, a fact evidenced by the presence of ovigerous females with ovaries in all the development phases. The species C. danae reproduces continuously, like most brachyurans from tropical waters.